Die Wortbildungslehre in der Anweisung zur Erlernung der Slavonisch-Rußischen Sprache (1705-1729) von Johann Werner Paus - Huterer, Andrea (Slavistische Beitraege, 2001)
The subject of the present study is the word formation theory in one of the oldest grammars of the Russian language, the instruction in 1705-29 to learn the Slavonic-Russian language, "For the benefit, especially the Teutschen Nation, aufgesetze" by Johann Werner Pause. The "instruction" is a central text of the so-called "dolomonovskij period rusistiki", i. the leisure of grammatical codification of Russian before the appearance of the first Russian grammar printed for native speakers, the "Rossijskaja grammatika" (1755/57) M.V. Lomonosov.